Two new species of calcareous sponges (Porifera: Calcarea) from the deep Antarctic Eckström Shelf and a revised list of species found in Antarctic waters - Rapp, Hans Tore; Göcke, Christian; Tendal, Ole Secher; Janussen, Dorte (Zootaxa, 2013)
The paper reports on two new species of calcareous sponges (Porifera, Calcarea) from the Antarctic Weddell Sea, Clathrina brandtae sp. nov. and Leucetta delicata sp. nov., collected at 600 m depth during the ANT XXIV/2-SYSTCO expedition in January 2008. The new species are described based on a combination of morphological and molecular data. With these new additions the number of species of calcareous sponges reported from south of 50°S (~south of the Polar Front) reaches 50 species. We report an exceptionally high degree of endemism within the group, and as many as 44 out of the 50 species of calcareous sponges are solely confined to Antarctic waters. An updated list of species of calcareous sponges from the area is provided.